Stand density and crown growth assessment of Anogeissus pendula Edgew in Tropical dry deciduous forests of Rajasthan (India) - Kumar, Manish; Poonia, Pawan Kumar; Ranawat, J. S.; Kumari, Sushil; Prahlad, V C (Indian Forester, 2022)
The present studies were carried out to assess the stand and crown growth of Anogeissus pendula (Dhav) in tropical dry deciduous forest at Jhalawar Forest Division, Rajasthan, India. Density of each site was determined by calculating the number of trees and basal area per hectare of the site. The results revealed that the Mishroli (S3) performed highest for growth parameters viz., dbh (26.20 cm), height (11.65 m), basal area (17.2 m2/ha), volume (37.73 m3/ha) and crown height (2.48 m) with lowest density (362.50 tree/ha), whereas, minimum has been observed for the same parameters at Bagher (S1)with highest density (535 trees/ha) and reverse is true for form factor (0.18) at above sites. Performance at Mishroli (S3) has been attributed to lower density, trees of higher diameter class indicates its site as good site quality compared to others. The poor performance at S1was attributed to high level of disturbance as observed in field. The crown level stand structure at S3 reported good performance for the parameters viz., crown width (8.89 m), crown length (9.46 m), crown basal area (63.62 m2/tree), crown index (1.07), crown percent (80.79 %), crown surface area (149.18 m2/tree). Crown projection ratio (44.99) and crown quotient to ground cover (3782.78) reported highest at Ghatoli (S4) and minimum (34.53) and (1213.02) at Mishroli (S3), due to high density level causing low mean dbh at S4 relatively to Mishroli (S3).